2010
DOI: 10.1590/s1984-82502010000100017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of analytical methods by direct and first-derivative UV spectrophotometry for evaluation of losartan potassium in capsules

Abstract: Losartan potassium is an antihypertensive non peptide agent, which exerts its action by specific blockade of angiotensin II receptors. The aim of the present study was the validation and application of analytical methods for the quality control of losartan potassium 50 mg in pharmaceutical capsules, using direct and first derivative UV spectrophotometry. Based on losartan potassium spectrophotometric characteristics, a signal at 205 nm of the zero order spectrum and a signal at 234 nm of the first derivative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Bonfilio et al [17] reported a direct and first-derivative UV-spectrophotometric method for determination of losartan in capsules. Based on losartan potassium spectrophotometric characteristics, a signal at 205 nm of the zero-order spectrum and a signal at 234 nm of the firstderivative spectrum were found adequate for quantification.…”
Section: Ultraviolet Spectrometrymentioning
confidence: 99%
“…Bonfilio et al [17] reported a direct and first-derivative UV-spectrophotometric method for determination of losartan in capsules. Based on losartan potassium spectrophotometric characteristics, a signal at 205 nm of the zero-order spectrum and a signal at 234 nm of the firstderivative spectrum were found adequate for quantification.…”
Section: Ultraviolet Spectrometrymentioning
confidence: 99%
“…It is the prototype of the thiazide group and antihypertensive drug. [2]  156  Rao, et al: Spectrophotometric method for losartan potassium and hydrochlorothiazide Literature survey reveals that LSP was determined by several methods including Spectrophotometric, [3][4][5][6] high performance liquid chromatography (HPLC) [6][7][8][9] and liquid chromatography, capillary electrophoresis and supercritical fluid chromatography. [10] HZ was determined by capillary electrophoresis [11] and electrochemical study [12] and by spectrophotometrically, [13][14][15][16][17] reverse phase-HPLC (RP-HPLC).…”
Section: Introductionmentioning
confidence: 99%
“…Olmesartan medoxomil was kindly supplied by Chemipharm Pharmaceutical Co. (6th of October, Egypt). The purity values of the studied drugs were 98.21 ± 1.22, 98.55 ± 1.54, 98.09 ± 0.89, and 98.66 ± 1.48 for losartan, irbesartan, valsartan, and olmesartan, respectively, and they were periodically checked via ultraviolet (UV)-spectrophotometry [2][3][4][5] and TLC measurements [6,26,[28][29], and no further purification steps were required. Chloroform and glacial acetic acid were of chromatographic grade (El-Nasr Pharmaceutical Chemicals, AboZaabal, Egypt).…”
Section: Methodsmentioning
confidence: 99%
“…The chemical structures of the studied drugs are shown in Figure 1. Different spectrophotometric [2][3][4][5][6][7] and spectroflourimetric [8][9][10] methods have been used for their quantification. Also, flow injection method was reported for their determination [11].…”
Section: Introductionmentioning
confidence: 99%